2018
DOI: 10.1016/j.stem.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A Linc1405/Eomes Complex Promotes Cardiac Mesoderm Specification and Cardiogenesis

Abstract: Large intergenic non-coding RNAs (lincRNAs) play widespread roles in epigenetic regulation during multiple differentiation processes, but little is known about their mode of action in cardiac differentiation. Here, we identified the key roles of a lincRNA, termed linc1405, in modulating the core network of cardiac differentiation by functionally interacting with Eomes. Chromatin- and RNA-immunoprecipitation assays showed that exon 2 of linc1405 physically mediates a complex consisting of Eomes, trithorax group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 38 publications
(52 reference statements)
2
91
2
Order By: Relevance
“…Eomes, a transcription factor participating in the control of developmental progression, was recruited to Mesp1 promotor by Linc1405. Meanwhile, it has been shown that the Linc1405/Eomes complex united WDR5 and GCN5 to activate Mesp1 in primitive streak, thereby promoting cardiac mesoderm specification and cardiogenesis [107].…”
Section: Lncrnas In Cardiac Developmentmentioning
confidence: 99%
“…Eomes, a transcription factor participating in the control of developmental progression, was recruited to Mesp1 promotor by Linc1405. Meanwhile, it has been shown that the Linc1405/Eomes complex united WDR5 and GCN5 to activate Mesp1 in primitive streak, thereby promoting cardiac mesoderm specification and cardiogenesis [107].…”
Section: Lncrnas In Cardiac Developmentmentioning
confidence: 99%
“…5l, S7b). These genes included early mesoderm transcriptional factors T [31][32][33][34][35][36][37], cardiac transcription factors GATA4, ISL1, TBX3, DES, NKX2.5, TBX5 and TBX18, and sarcomeric genes CTNT, MYH7 (Figs. 5m-n).…”
Section: Atac-seq Reveals Global Alterations Of Chromatin Remodeling mentioning
confidence: 99%
“…During PSC differentiation, Tbx6 promoted mesoderm and endoderm induction in the absence of serum and growth factors in both a cellautonomous and non-cell-autonomous manner (Sadahiro et al 2018). Further studies in mouse will be required to determine how the precise domain of Mesp1 expression is defined within the nascent mesoderm, although other factors are also implicated in early specification of cardiac progenitors, such as long non-coding RNAs (Klattenhoff et al 2013;Ounzain et al 2015;Guo et al 2018), which have even been used to promote trans-differentiation to cardiac cell types (Hou et al 2017) (Figure 3).…”
Section: Mesp1mentioning
confidence: 99%